HUBUNGAN MOTIVASI DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMA MODEL AL-KHAWARIZMI PULAU SEBUKU - Agus Syarifuddin (STKIP Paris Barantai, 2016)
The purpose of this research of mutual knowing (1) the relationship between motivation to learn the results of high school students learning mathematics model Al-Khwarizmi Sebuku Island School Year 2015/2016. (2) To examine the relationship between interest in learning the results of high school students studying Mathematics Model Al-Khwarizmi Sebuku Island School Year 2015/2016. (3) To examine the relationship between motivation and interest in learning the learning outcomes of students of Mathematics Model Al-Khwarizmi Sebuku Island School. The method used in this research is descriptive quantitative analysis. The population in this study were high school students Model Al-Khwarizmi Sebuku Island totaling 79 people, while the sample are students of class X and XI High School Model Al-Khwarizmi Sebuku Island totaling 59 people. The sampling technique used in this study is that the probability sampling random.Teknikanalisis data in this study using a simple correlation and double correlation . Teknik data collection was conducted by questionnaire and documentation. Results obtained by the questionnaire and the results of student learning Mathematics. (1) There is a positive relationship between motivation and learning outcomes of study Mathematics with a relatively high coefficient of 0,778. (2) There is a positive and significant correlation between interest in learning the results of learning mathematics students with a relatively high coefficient of 0,674. (3) Based on the results turned out to be greater than F or Ftabel 40.23> 3.16, then Ho is rejected and Ha accepted means there is a positive and significant correlation between motivation and interest in learning about the mathematics and the relationship contributed 66.3% of high school students in Al-Khwarizmi Model Sebuku Island. Keywords: Motivation And Interest Related Learning